Renewable thermoplastics – Starch fatty acid esters as alternatives to synthetics - Peggy Hermann; Thomas Heinze (BioResources)
Thermoplastics are an important class of polymers that find widespread use in a broad variety of applications. Because of environmental concerns regarding the lack of biodegradability of synthetic thermoplastics, green alternatives are increasingly studied that should be both based on renewable resources and biodegradable. In this regard, polysaccharide esters of naturally occurring fatty acids are in the center of interest.